2020
DOI: 10.9734/cjast/2020/v39i830598
|View full text |Cite
|
Sign up to set email alerts
|

Selection Criteria for Identification of High Yielding Rice (Oryza sativa L.) Genotypes under Aerobic Cultivation

Abstract: Ten rice genotypes were evaluated to study the genetic variability, correlation and path analysis under aerobic conditions for selection of high yielding genotypes. The experiment is carried out in RCBD with 3 replications and the data is analysed in SPAR 2.0, Past 4.01 and OPSTAT for variability, correlation and path analysis respectively. The phenotypic and genotypic coefficients of variation were high for the number of productive tillers per plant, the number of filled grains per panicle, 1000-grain weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results of this study indicate that the genotypic treatment has a significant effect on all observed traits (13). The real genotypic treatment means that there are differences in the genetic makeup contained in all the genotypes used, (Rathod et al, 2020). The correlation (closeness of relationship) between a trait and the desired trait (outcome) will be very helpful in selecting certain traits that will contribute most significantly to the results so that they will be used in the selection process.…”
Section: Correlation Between Traitsmentioning
confidence: 99%
“…The results of this study indicate that the genotypic treatment has a significant effect on all observed traits (13). The real genotypic treatment means that there are differences in the genetic makeup contained in all the genotypes used, (Rathod et al, 2020). The correlation (closeness of relationship) between a trait and the desired trait (outcome) will be very helpful in selecting certain traits that will contribute most significantly to the results so that they will be used in the selection process.…”
Section: Correlation Between Traitsmentioning
confidence: 99%